Management of Tourist Developments and Tourist Trips (International Journal of Current Engineering and Technology, 2014)
Management of tourism developments in Kosovo is a separate issue which has to do with the importance of tourism, landscapes and tourist trips as important components of urban and sub- urban areas. Identifying tourist’s managing problems can document the experiences and characteristics , tourist and conservation tools to study continuous landscapes towards improving their tourism value . In this paper are presented for potential centers of these landscapes and tourist trips , which have a common goal , to provide potential tourists are concentrated as well as essential for the successful management of the tourism industry. Basically, landscapes are parks or gardens or cultural sites of various historical contexts. This potential determines the overall scope of the special issue and considers the relationship between ecotourism, tourism, landscapes and tourist satisfaction. It then describes and summarizes several key points, ends by claiming that tourism landscapes are suitable for general and ecological success. Movement of conservation and preservation of indigenous value - system of local communities, with many social, economic and cultural benefits.
Keywords: Management, culture, ecotourism , landscapes , trips